Simulador de curvas de pressão requerida e disponível para poços petrolíferos - Souza, João Marcos Fontinele de Oliveira (Brasil, 2021)
In the oil industry, plotting the Inflow Perfomance Relationship (IPR) and Tubing Perfomance Relationship (TPR) under the same graph makes it possible to perform a nodal analysis of an oil well. Such analysis is important to identify the operation points, as well as the need to implement equipmentsin production. Currently, there are simulators in the industry able to perform the plotting and analysis of these curves, however, their acquisition is costly, which makes them unfeasible in most universities. This work aims to develop a simulator capable of plotting IPR and TPR curves from resevoir and well characteristics. For such, Microsoft Excel software was used to develop the curves and Visual Basic for Applications (VBA) was used to create an interactive user interface. The validation of the computational tool was made through comparisons with results presented in the literature. In general, the results obtained was proven to be excelent, thus, showing that the tool is able to support the academic community.